PENGARUH TINGKAT KOMPETENSI SUMBER DAYA MANUSIA, TEKNOLOGI INFORMASI, PENGENDALIAN INTERN DAN PENGAWASAN KEUANGAN TERHADAP KEANDALAN PELAPORAN KEUANGAN KEPOLISIAN RESORT PROVINSI JAWA TIMUR - Iskha Rimah; Harmono Harmono; Sihwahjoeni Sihwahjoeni (Jurnal Akuntansi Trisakti, 2021)
The purpose of this research is to be able to determine the competence of human resources, technology and information, internal control, and financial control on the reliability of a financial report at the East Java Provincial Police. The type of this research is quantitative, in this research the method that will be used in this research is the census method on members of the police who work as treasurers in the financial department of the East Java Police, of which there are 50 people as respondents, while the data analysis technique used is multiple linear regression. . The research results found that HR competence had a significant effect on the reliability of financial reports at the East Java Police, technology and information had no effect on the reliability of financial reports at the East Java Police, internal control had a significant effect on the reliability of financial reports at the East Java Police